154 Early Evolution of a Minimally Invasive Mitral Programme. (3rd June 2016) - Jones, Sion; Palmer, Ken; Al-Rawi, Omar; Modi, Paul
Abstract : Introduction: Minimally invasive mitral valve (MIMV) surgery is technically challenging with a long learning curve. We examined the evolution of repair techniques in a new program. Methods MIMV surgery at our institution is performed through a 6 cm right anterior minithoracotomy. We examined prospectively collected data on all patients undergoing MIMV between March 2011 and December 2014. Data are presented as medians (interquartile range). Results 99 patients had MIMV procedures during this period. Median age was 61 (53 to 68) years, 31 (31%) were female, 2 were reoperations. The repair rate for degenerative and functional disease was 94% (84 of 89 patients) with no/trivial residual MR (n = 82, 98%) or mild MR (n = 2, 2%) on the intra-operative echo. All rheumatic valves were electively replaced. Twenty (20%) patients underwent concomitant procedures: cryomaze (n = 13), patent foramen ovale closure (n = 6), tricuspid valve repair (n = 3). Bypass and clamp times were 196 (170 to 221) and 132 (111 to 150) minutes respectively. There was one conversion to sternotomy for mild residual MR found after femoral decannulation; this patient left hospital 6 days later with no regurgitation. There was no mortality and no strokes. Duration of ventilation, ITU and hospital stay were 8 (6–10) hours, 2 (1–3) and 6 (5–8) days respectively. When examined by tertile, the use of GoreTex loops increased significantly as the programme progressed (p < 0.001) while resective techniques declined (p < 0.001). Conclusions High rates of valve repair are achievable with minimally invasive mitral surgery. There has been a significant change in the repair techniques employed as the programme developed.